Cost Effectiveness Analysis of Antibiotics Use Prophylactic in Caesarean Surgery Patients at Dirgahayu Hospital Samarinda - Maulida, Baidha' Rahma; Hanifa, Deasy Nur Chairin (JURNAL FARMASI DAN ILMU KEFARMASIAN INDONESIA, 2025)
Background: Caesarean delivery carries the risk of complications, such as surgical wound infection. Surgical wound infections can be prevented by administering prophylactic antibiotics, which have been proven to reduce the risk of surgical wound infections. Various types of prophylactic antibiotic use affect the costs incurred during treatment; therefore, it is necessary to carry out a cost-effectiveness analysis to determine treatment options with the best effectiveness and low cost. Objective: This study aimed to determine the cost-effectiveness of using prophylactic antibiotics in patients undergoing caesarean sections at Samarinda City Hospital. Methods: This research used an observational approach with retrospective data collection using medical record data from January 2023 to September 2024, with sampling using total sampling. In this study, 75 samples were obtained that met the inclusion and exclusion criteria of the study. Results: The results of the study showed that the prophylactic antibiotics used in caesarean section patients were cefotaxime, ceftriaxone, and cefazolin. Based on the cost-effectiveness analysis, cefazolin was more cost-effective than cefotaxime and ceftriaxone in patients undergoing caesarean section, with an ACER value of IDR 123,998, and was included in quadrant II. Conclusion: Cefazolin IV (1 g) is a cost-effective prophylactic antibiotic for caesarean section patients at Dirgahayu Hospital Samarinda, with 100% therapeutic effectiveness and low costs based on the average total cost, ICER calculation, cost-effectiveness grid analysis, and cost-effectiveness plane.